Encyclopedia of interest groups and lobbyists in the United States. - Ness, Immanuel (Sharpe Reference, 2000)
Provides information about a variety of organizations, arranged alphabetically within such groupings as Agriculture, Environmental, Health, Labor, and Political, Ideological and Religious.